If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + -9 + 3 = 24 Reorder the terms: -9 + 3 + 3n = 24 Combine like terms: -9 + 3 = -6 -6 + 3n = 24 Solving -6 + 3n = 24 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3n = 24 + 6 Combine like terms: -6 + 6 = 0 0 + 3n = 24 + 6 3n = 24 + 6 Combine like terms: 24 + 6 = 30 3n = 30 Divide each side by '3'. n = 10 Simplifying n = 10
| 3(14-4y)-5y=-9 | | 6y+5=10y-1 | | 12k+14=10k-2k-7 | | -3(x+4)+16= | | J-8=-5 | | 10x-8=31.5 | | 2(2x-11)=2x | | 8x-4+8x-4+21+3=180 | | 9x^2-42x+37=0 | | 11-3(x+4)+5= | | H-41=13 | | 24=3(x)-6 | | (10x+36y)+(2x+y)= | | 63=60.50p+17.50 | | 8x-4+8x-4+4+3=180 | | 9=3(x)-6 | | 152+8h= | | 19=b-3 | | -3=3(x)-6 | | -6.5z+7.5z= | | 4n-2=12-4n | | 7(15x+25y)=125 | | x^2+4y^2=144 | | -12=3(x)-6 | | 12x+6=4x-20-2 | | 5+3y=30 | | -24=3(x)-6 | | 2x^2y+8xy-58y=0 | | 5x+55=7x+185 | | 2(7h-5)=24+9h | | -2x+19+5x-11= | | 9(x-2)-3=-21 |